Niosomes entrapment capacity of ketoprofen and prediction transdermal administration - rahman, Latifah; Ismail, Isriany; Wahyudin, Elly (Indonesian Journal of Pharmacy, 2011)
Niosomes  are  vesicles  system  that  have  applications in  the  delivery  of lipophilic,hydrophilic  and  amphiphilic  drugs.  Ketoprofen,  is  very  insoluble  in water  and  cause  gastric  irritation  when  taken  orally.  It  is  very  important  to develop a transdermal delivery system for ketoprofen. This research was aimed to  design  niosomes  which  can  deliver  ketoprofen  via transdermal  route. Experiments  were  designed  to  incorporate  ketoprofen into  niosomes   with  lipid film  hydration  method.  Lipid  mixture  consist  of  cholesterol  and  sorbitan  ester (span  20,  60,  80).  Niosomes  which  can  deliver  ketoprofen  trough  the  skin barrier  determined  by  calculating  amount  of   ketoprofen  in  the  blood  of  rabbit. The  type  of  sorbitan  ester  was  chosen  based  on  the  highest  drugs  entrapment and  ketoprofen  as  drugs  model.  Preparation  of  niosomes  was  optimized  for  the highest  percent  drug  entrapment  by  increasing   molar  concentration  of  lipidmixture  with  the  stable  comparison  of  1:1.  This  research  result  are  niosomes with  lipid  mixture  span  60  and  cholesterol  have  the highest  drug  entrapment efficiency  of  niosomes  66.16%  with  range  size  1–6  µm.  Niosomes  can  deliver ketoprofen  to  the  systemic  circulation  via  transdermal  route  with  plasma  level concentration achieved in 1.5 hour.Key words: niosomes, ketoprofen, transdermal